2014
DOI: 10.1016/j.carbon.2013.12.087
|View full text |Cite
|
Sign up to set email alerts
|

EELS analysis of Nylon 6 nanofibers reinforced with nitroxide-functionalized graphene oxide

Abstract: A detailed analysis by transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) of nitroxide-functionalized graphene oxide layers (GOFT) dispersed in Nylon 6 nanofibers is reported herein. The functionalization and exfoliation process of graphite oxide to GOFT was confirmed by TEM using electron diffraction patterns (EDP), wherein 1 to 4 graphene layers of GOFT were observed. The distribution and alignment of GOFT layers within a sample of Nylon 6 nanofiber reveals that GOFT platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…When discharged, the peak intensity of N‐6 and N‐Q is found to clearly decrease to some extent, which may be caused by coverage of N‐6 and partial N‐Q active sites by Li 2 CO 3 product and detecting hardly by the surface‐sensitive XPS. When recharged, all of these peaks reappeared (Figure n) …”
mentioning
confidence: 98%
“…When discharged, the peak intensity of N‐6 and N‐Q is found to clearly decrease to some extent, which may be caused by coverage of N‐6 and partial N‐Q active sites by Li 2 CO 3 product and detecting hardly by the surface‐sensitive XPS. When recharged, all of these peaks reappeared (Figure n) …”
mentioning
confidence: 98%
“…[ 30 ] A proposed functionalization mechanism of GO with oxoammonium salts (Br‐TEMPO) to produce nitroxide‐functionalized graphene oxide (GOFT) has been reported by our work group before (Figure S1, Supporting Information). [ 28,31 ]…”
Section: Figurementioning
confidence: 99%
“…Electrospinning provides electrostatic stretching forces (whipping elongation) for overcoming any entanglement of nanomaterials [70]. A uniform distribution of carbon nanomaterials is critical for preventing nanofiller protrusion, notches, and beads across the fibre body [56,70]. Polymer solution properties, such as molecular weight, solution viscosity, surface tension, solution conductivity, and dielectric constant, are critical factors that affect the electrospun fibre morphology [68,83,84].…”
Section: Morphology Of the Electrospun Fibresmentioning
confidence: 99%
“…This behaviour is due to the converging nanoscale jet reducing the number of available orientations in the flow field [53]. NGO was aligned within the PA6 nanofibres meanwhile agglomerates of the nanofiller could hardly be aligned; therefore the NGO sheets protruded from the fibres; Figure 7 shows the NGO/PA6 nanofibres [56]. Zomer Volpato et al found that the surface of PA6 electrospun fibres was rough with defects attributed to the fibre stretching and the presence of O-MWCNTs in the nanocomposite fibres resulted in greater surface roughness compared to the control nanofibres [53].…”
Section: Morphology Of the Electrospun Fibresmentioning
confidence: 99%